Assessing The Influence Of Leadership Styles On Organizational Innovation In The Technology Sector - Marc Dupont; Philippe De Clercq (International Journal of Economics and Management Sciences, 2024)
This article examines the effect of different leadership styles on fostering innovation within technology companies. By analyzing data from tech firms, the research highlights how transformational, transactional, and laissez-faire leadership styles impact employee creativity, collaboration, and the adoption of new technologies. The study concludes that transformational leadership is most effective in driving innovation and sustaining competitive advantage in the tech industry.